Long Container Dwell Time at Seaport Terminals: An Investigation Study from a Consignee Perspective - Ewamer, Ammar Gamal Mohamed Khlil; Menyhárt, József (International Journal of Engineering and Management Sciences, 2022)
Many companies are concerned about the problem of increasing average dwell time for their import containers at the port of the final destination and therefore incurring additional shipping costs in form of demurrage charges for the port administration and detention charges for the shipping line. Previous studies have addressed this topic by analyzing terminal operations and evaluated its effects on port productivity and competitiveness; however few studies have explicitly explored long container dwell time causes from a consignee perspective. This research aims to identify the causes of long dwell time for the import containers at port storage yards for one of the leading FMCG companies in Jordan. To that end, the data of import containers whose stay at the terminal exceeded the free storage days in the period between 2019 and 2020 were collected by referring to the set of shipping documents and reviewing the correspondences between the consignee and other parties in the supply chain. Based on the timelines that have been analyzed for each case of delay to the collection of shipping documents in consideration with the payment terms, as well as the clearance and delivery timelines, ten causes for the long container dwell time have been identified and classified into three main categories according to the types of flow in the supply chain; five causes related to information flow, two causes related to cash flow, and three causes related to physical flow. The impact of these causes has been evaluated using the demurrage and detention charges as a measure indicator and the findings of this research have also revealed that the causes related to cash flow have a greater impact than the other types of causes.